Energetic fitness: Field metabolic rates assessed via 3D accelerometry complement conventional fitness metrics. (13th March 2018) - Grémillet, David; Lescroël, Amélie; Ballard, Grant; Dugger, Katie M.; Massaro, Melanie; Porzig, Elizabeth L.; Ainley, David G.
Abstract: Evaluating the fitness of organisms is an essential step towards understanding their responses to environmental change. Connections between energy expenditure and fitness have been postulated for nearly a century. However, testing this premise among wild animals is constrained by difficulties in measuring energy expenditure while simultaneously monitoring conventional fitness metrics such as survival and reproductive output. We addressed this issue by exploring the functional links between field metabolic rate (FMR), body condition, sex, age and reproductive performance in a wild population. We deployed 3D accelerometers on 115 Adélie penguins Pygoscelis adeliae during four breeding seasons at one of the largest colonies of this species, Cape Crozier, on Ross Island, Antarctica. The demography of this population has been studied for the past 18 years. From accelerometry recordings, collected for birds of known age and breeding history, we determined the vector of the dynamic body acceleration (VeDBA) and used it as a proxy for FMR. This allowed us to demonstrate relationships among FMR, a breeding quality index (BQI) and body condition. Notably, we found a significant quadratic relationship between mean VeDBA during foraging and BQI for experienced breeders, and individuals in better body condition showed lower rates of energy expenditure. We conclude that using FMR as a fitness component complementary to more conventional fitness metrics will yield greater understanding of evolutionary and conservation physiology. A plain language summary is available for this article. Abstract : Plain Language Summary